2004
DOI: 10.1111/j.1432-1033.2004.04446.x
|View full text |Cite
|
Sign up to set email alerts
|

pH dependence, substrate specificity and inhibition of human kynurenine aminotransferase I

Abstract: Human kynurenine aminotransferase I/glutamine transaminase K (hKAT-I) is an important multifunctional enzyme. This study systematically studies the substrates of hKAT-I and reassesses the effects of pH, Tris, amino acids and a-keto acids on the activity of the enzyme. The experiments were comprised of functional expression of the hKAT-I in an insect cell/baculovirus expression system, purification of its recombinant protein, and functional characterization of the purified enzyme. This study demonstrates that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
136
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 97 publications
(145 citation statements)
references
References 43 publications
(78 reference statements)
6
136
2
1
Order By: Relevance
“…When the phosphate and borate buffer mixture, adjusted to pH 6.0 to 11.0, was used to prepare mKAT III-kynurenine-glyoxylate reaction mixtures, mKAT III displayed optimum activity around pH 9.0 to 10.0 (Fig. 1B), which is close to the optimum pH reported in the literature (3,4,16,49) for mammalian brain KAT I but apparently different from the optimum pH (7.5 to 9.0) of recombinant hKAT I (25). mKAT III was tested for aminotransferase activity toward 24 different amino acids, using glyoxylate as a primary amino group acceptor.…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…When the phosphate and borate buffer mixture, adjusted to pH 6.0 to 11.0, was used to prepare mKAT III-kynurenine-glyoxylate reaction mixtures, mKAT III displayed optimum activity around pH 9.0 to 10.0 (Fig. 1B), which is close to the optimum pH reported in the literature (3,4,16,49) for mammalian brain KAT I but apparently different from the optimum pH (7.5 to 9.0) of recombinant hKAT I (25). mKAT III was tested for aminotransferase activity toward 24 different amino acids, using glyoxylate as a primary amino group acceptor.…”
Section: Resultsmentioning
confidence: 52%
“…The substrate profile of mKAT III overlaps considerably with that of hKAT I (25), but hKAT I favors hydrophobic substrates and mKAT III prefers hydrophilic substrates. For example, mKAT III has high transamination activity toward asparagine, for which hKAT I has essentially no activity (25). Kinetic data provided an overview regarding the catalytic efficiency of mKAT III toward individual amino acids (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they exhibit catalytic efficiencies quite different from those of the amino acids mentioned above. hKAT I is more efficient in transaminating hydrophobic amino acids (such as phenylalanine, leucine, and tryptophan), while AeKAT is more efficient in transaminating relatively hydrophilic amino acids (such as cysteine, histidine, tyrosine, and methionine) (4,5). Upon superposition of a dimer of the AeKATcysteine complex onto the hKAT I-phenylalanine structure ( Figure 6A), we identified the residues within 5 Å of both ligands and found that most residues were the same.…”
Section: Discussionmentioning
confidence: 99%